EFEKTIVITAS TERAPI MUSIK TERHADAP PENURUNAN STRES KERJA PERAWAT DI INSTALASI RAWAT JALAN RUMAH SAKIT UMUM HARAPAN IBU PURBALINGGA PADA MASA PANDEMI - ERINA Ina Rina; Dwi Novitasari; Ikit Netra Wirakhmi (Universitas Harapan Bangsa Purwokerto, 2020)
ABSTRACT The Covid pandemic has become a threat to health for people in the world, including Indonesia. Nurses as the vanguard provide an important role in handling Covid-19. However, working can not be separated from challenges faced. These challenges can be stressful for nurses. Work stress is a response that is not specific to the demands obtained which gives an impact on a person's physical and psychological condition. The perceived stress will have an impact on one's performance, therefore, stress must be avoided. Listening to music is one way to reduce work stress levels. The purpose of this study is to determine the effectiveness of music therapy to reduce the work stress of nurses in the Outpatient Department of Harapan Ibu Purbalingga Hospital. The method used was the pre-trial design with the one group pre-test-post-test method. The measuring instrument used was a job stress questionnaire. The research sample used wasa total sampling technique of 31 people. The results of data analysis shows that the work stress level of nurses before being given music therapy was at most in the category of work stress level of 61.3%. Meanwhile, after being given music therapy, the work stress level of nurses was in the category of mild stress level of 96.8%. The results of the paired sample-test showed p value <α 0,000 or p <α 0.05. The conclusion of this study is that there is the difference in the work stress level of nurses before and after being given music therapy, music therapy is effective in reducing the work stress of nurses in the Outpatient Department of Harapan Ibu Purbalingga Hospital. Keywords: Music Therapy, Work Stress, Covid-19